Female Employment Peculiarity in Crisis Industries - ЖидковаЕлена Михайловна (Journal of Economic Sociology, 2010)
The goal of the paper is to disclose the peculiarities of female employment in contemporary female enterprises. How the expectations and ambitions of working class women contribute to the additional stability of the companies in the crisis female industries? The paper is based on the results of the project ISITO “Management and labour relations: management practices in contemporary Russian companies” (2002-2006)